Development of alpha-SiAlON-SiC ceramic composites by liquid phase sintering - Souza, J. V. C.; Santos, C.; Kelly, C. A.; Silva, O. M. M. (Elsevier B.V., 2007)
In this work, in situ alpha-SiAlON-SiC ceramic composites were obtained,by, liquid phase sintering, using SiC as reinforcement. Different beta-SiC powder contents (0-20 wt.%), were added to Si3N4-AlN-RE2O3. powder mixtures, and compacted by cold isostatic pressing. The samples were sintered at 1950 degrees C for 1 h, in N-2 atmosphere. Sintered: samples were characterized by relative density, weight loss, X-ray diffraction and scanning electron microscopy. Furthermore, mechanical properties such as hardness and fracture toughness were determined by Vickers indentation method. Lattice parameters of the alpha' phase did not considerably change with increase of SiC content. However, morphology, average grain size and aspect ratio of the alpha' phase were considerably changed with increase of the SiC content. These behavior influences significantly the mechanical properties of this hard ceramic composite. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: alpha-SiAlON; beta-SiC; silicon carbide; composites; sintering; microstructure; mechanical properties